Regularização fundiária como política pública: o caso de Santana de Parnaíba, região metropolitana de São Paulo - Tavares, Fabiana Faria (2021)
The object of this work is the study of urban land tenure regularization carried out in the city of Santana de Parnaíba, located in the Metropolitan Region of São Paulo, 35km from the capital. Through a detailed analysis of urban land tenure regularization carried out between 2014 and 2020, the work discusses all stages of this process and the results achieved, making the interrelationship of these results with the academic debate. Analyzing the evolution and innovations, it aims to create a new vision about the process, which becomes a much more complex instrument than simply being or not being effective in real estate titles. As a result, the work emphasizes the importance of this type of urban instrument, its numerous products and its use as public policy in management. Knowing a case such as the land tenure regularization carried out in Santana de Parnaíba can broaden horizons and improve public policies in the country.